Émile-G. Léonard e sua contribuição aos estudos do protestantismo brasileiro - Carvalho, Marcone Bezerra (2013)
French historian Émile-G. Léonard, while residing in Brazil (1948-1950) and teaching at the Universidade de São Paulo (USP), made an assessment of the Protestant segment in Brazil. He wrote a work that, six decades later, still constitutes the main interpretation of the Brazilian Protestant movement. This Sorbonne chair professor was influenced by the Annales School (especially by Lucien Fevbre) and was the first historian of this movement to consider Brazil as an object of research. This thesis approaches, firstly, the scenario of contemporary historiography and its impact within or on the overall context of the country. Next, it presents an overview of Léonard s life and work, with special attention given to his production about Brazil, that is to his Brazilianism . The last chapter deals with his evaluation of Brazilian Protestantism, and analyzes his contribution and influence with respect to studies developed around this theme.